Area array packaging processes for BGA, Flip Chip, and CSP - Gilleo, Ken (McGraw-Hill, 2004)
This engineering reference covers the most important solders and materials in modern electronic packaging. Written by a team of world-class professionals and researchers, Area Array Packaging Materials includes vital information necessary for the design of cutting-edge electronics products.